L.D. Trotsky and Activity of Research and Technology Division of USSR Supreme Council of National Economy in mid-1920s - Y G Isaevitch (RUDN Journal of Russian History, 2013)
The article considers the activities of L.D. Trotsky as the head of the Research and Technology Division of the Supreme Council of National Economy of the USSR in 1925–1926. The author uses archival documents from the Fund of the Russian State Archive of Economy, documents from the Russian State Archive of Social and Political History and other sources. There is analyzed L.D. Trotsky’s contribution to the development of applied science in the USSR.